2009
DOI: 10.1038/nchembio.199
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric communication between protomers of dopamine class A GPCR dimers modulates activation

Abstract: A major obstacle to understanding the functional importance of dimerization between Class A G protein-coupled receptors (GPCRs) has been the methodological limitation in achieving control of the identity of the components comprising the signaling unit. We have developed a functional complementation assay that enables such control and illustrate it for the human dopamine D2 receptor. The minimal signaling unit, two receptors and a single G protein, is maximally activated by agonist binding to a single protomer,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

29
301
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 309 publications
(336 citation statements)
references
References 51 publications
29
301
1
Order By: Relevance
“…Asymmetric agonist binding to WT GPCRs is compatible with the current notion that assumes that activation of one GPCR protomer is not only sufficient, but may favour signal transduction within a GPCR complex 28,29,44 . Indeed, binding of an agonist to one protomer is able to activate a dopamine D2 receptor homomeric complex, and binding of an inverse agonism to the second site enhances signalling 28 .…”
Section: Di(oligo)merization Ofsupporting
confidence: 80%
See 2 more Smart Citations
“…Asymmetric agonist binding to WT GPCRs is compatible with the current notion that assumes that activation of one GPCR protomer is not only sufficient, but may favour signal transduction within a GPCR complex 28,29,44 . Indeed, binding of an agonist to one protomer is able to activate a dopamine D2 receptor homomeric complex, and binding of an inverse agonism to the second site enhances signalling 28 .…”
Section: Di(oligo)merization Ofsupporting
confidence: 80%
“…Indeed, binding of an agonist to one protomer is able to activate a dopamine D2 receptor homomeric complex, and binding of an inverse agonism to the second site enhances signalling 28 . However, as reported by Han et al 28 , this asymmetry is not only observed with ligand-induced conformational selection but also beyond ligand-binding cooperativity, because agonist-independent activation in a constitutive receptor is enough to propagate an inhibitory effect to the partner receptor and decrease the efficacy of the homomeric complex. A clear case of an asymmetric binding mode has been dissected in chemokine receptor homo-and hetero-mers (reviewed in ref.…”
Section: Di(oligo)merization Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…Of particular interest in this field are recent developments in protein-protein docking software that lead to the prediction of the possible binding sites between two molecules, allowing the formation of a stable complex (Simpson et al, 2010;Kaczor et al, 2015;Soni and Madhusudhan, 2017). Examples of this approach include the study of the lutropin receptor dimerization (Fanelli, 2007), studies aimed at characterizing the interaction interface in serotonin (5-HT) 4 (Bestel, 2005;Soulier et al, 2007) and rhodopsin complexes (Han et al, 2009), and the generation of models for the heterodimeric mGluR 2 -5-HT 2A complex (Bruno et al, 2009) and for the dopamine D 1 -D 2 receptor dimer ). -Molecular dynamics and coarse-grained simulations are one of the most versatile and widely applied computational techniques for the study of membrane proteins (Almeida et al, 2017), as they consider the tertiary structure of the studied proteins and can implement an energy landscape to estimate the molecular interactions, also accounting for the role of the lipid microenvironment.…”
Section: Interaction Interfacesmentioning
confidence: 99%
“…However, fluorescence labelling and radioligand binding have revealed only cis activation for chimeric heterodimers of rhodopsinlike leukotriene B 4 receptors (Damian et al, 2008). Asymmetric activation was reported for G protein-fused dopamine D 2 receptor homodimers via functional complementation experiments (Han et al, 2009). Agonist binding to a single protomer induced full activation.…”
Section: Structural Symmetry and Transient Asymmetry Of Signalling Prmentioning
confidence: 99%